1983
DOI: 10.3382/ps.0620405
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Atrophy in Gallus domesticus Fed Acute Doses of Copper Fungicides

Abstract: Acute oral toxicity of the copper fungicides, copper sulphate and copper oxychloride, were studied in male Gallus domesticus. The median lethal dose for copper sulphate and copper oxychloride determined were 693 and 1263 mg/kg body weight, respectively. Severe diarrhea and delayed mortality (3 to 6 days) was characteristic of copper oxychloride. Liver weights were nearly doubled in birds fed copper oxychloride and marked dose-dependent testicular atrophy was noticed in both copper sulphate and copper oxychlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…In our case, surface erosions and ulceration of the mucous membrane of the gizzards as well as liver congestion were observed in all examined birds. Our findings concur well with the results of an experiment on White Leghorn males fed with acute doses of 2 Cu compounds (Shivanandappa et al, 1983). The authors described the impairment of spermatogenesis concomitant with testicular atrophy, congestion of the liver and kidneys and high mortality that occurred within 24 to 28 h in birds fed with CuSO 4 .…”
Section: Discussionsupporting
confidence: 93%
“…In our case, surface erosions and ulceration of the mucous membrane of the gizzards as well as liver congestion were observed in all examined birds. Our findings concur well with the results of an experiment on White Leghorn males fed with acute doses of 2 Cu compounds (Shivanandappa et al, 1983). The authors described the impairment of spermatogenesis concomitant with testicular atrophy, congestion of the liver and kidneys and high mortality that occurred within 24 to 28 h in birds fed with CuSO 4 .…”
Section: Discussionsupporting
confidence: 93%
“…For the hematological findings, all lactating dams treated with different doses of COC (147 and 73.5 mg/kg Bw. COC) showed that there was a significant decrease in RBCs count, Hb content and PCV in all treated dams with elevation in leukocytic counts and as well [9] reported that copper oxychloride may accumulate in various tissues as a heavy metal and cause hemolytic anemia, also [26] found that copper may promote hemolysis anemia and hemorrhage with abnormal high blood Cu+ levels . However, the elevation of the leukocyte counts considered as a precise indicator of the immune system, defense mechanism and increase in the inflammatory response upon exposure to environmental pollutant and pesticides [27].…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, COC confirmed to inhibit spermatogenesis and affect the function of leydig cells with steroidogenic inhibition and cholesterol accumulation in such cells, such reproductive toxic effect may be due to Cu+ capability of interaction with other metals as selenium, iron and zinc and in turn affect their absorption through antagonism resulted in a deficiency of such element with subsequent cellular dysfunction with deleterious effect on the testes (19,27) The toxic effect of copper on the follicular waves also observed in female mouse ovaries (intraperitoneal injection of 70mg/ kg of CuCl2in adult female mice) and the results revealed a significant increase in stage II follicles with degeneration and apoptosis of oocytes and oocyte fragmentation in treated groups than control (39) even in earthworm Eisenia fetida the cocoon production and hatchling were significantly reduced upon exposure for different concentrations of copper oxychloride (40).…”
Section: General Toxicity Of Copper Oxychloridementioning
confidence: 96%
“…Copper is considered an essential micronutrient and many animals can cope with excess copper exposure by the liver but the overwhelming of such mechanism may occur with repeated exposure (15) resulting in hemolysis, anemia, diarrhea, hemorrhage, kidney failure, and death of animals (19).…”
Section: Copper Metabolism In Living Organismsmentioning
confidence: 99%